Modulating CD4+ T Cell Migration in the Postischemic Liver: Hepatic Stellate Cells as New Therapeutic Target?. Issue 1 (January 2015) - Reifart, Jörg; Rentsch, Markus; Mende, Konstantin; Coletti, Raffaele; Sobocan, Monika; Thasler, Wolfgang E.; Khandoga, Andrej
Abstract : Background: CD4+ T cells play a critical role during hepatic ischemia-reperfusion (I/R) injury although the mechanisms of their migration in the postischemic liver remain unclear. We answered the questions of whether hepatic stellate cells (HSCs) interact with CD4+ T cells during I/R of the liver and whether modulation of HSC activity affects T cell–dependent I/R injury. Methods: In mice, migration of CD4+ T cells was analyzed in vivo using conventional intravital microscopy and two-photon microscopy. CD4+ T cell-HSC interactions were visualized after infusion of fluorescence-labeled CD4+ T cells into Cx3CR1 mice (mice exhibiting GFP-labeled HSCs) after I/R. Because the activation of HSC is controlled by endocannabinoid receptors, CB-1 and CB-2, the mice received treatment before I/R with the CB-2 agonist JWH-133 to reach HSC depletion or the CB-1 agonist arachidonylcyclopropylamide to activate HSCs. Sinusoidal perfusion and liver transaminases were used as markers of I/R injury. Results: Hepatic I/R induced CD4+ T cell recruitment in sinusoids. More than 25% of adherent CD4+ T cells were colocalized with HSCs during reperfusion, suggesting a direct cell-cell interaction. The HSC deactivation with JWH-133 significantly attenuated the CD4+ T cell recruitment in the postischemic liver and reduced I/R injury as compared to the vehicle-treated group. The HSC hyperactivation by CB-1, however, did not affect T-cell migration and even increased perfusion failure. Conclusion: Our in vivo data suggest that CD4+ T cells interact with HSCs on their migration into the hepatic parenchyma, and a depletion or deactivation of HSCs protects the liver from T cell–dependent I/R injury. Abstract : The interaction of hepatic stellate cells and CD4+ T cells is relevant in ischemia reperfusion injury of the liver, with attenuated T cell recruitment shown with deactivated hepatic stellate cells.